Auditing within service-oriented architecture: the Dutch experience. (1st January 2013) - Guah, Matthew Waritay; Onyeocha, Joseph C.
SOA is an unsolved problem for IT infrastructures yet its treatment in mainstream accounting literature is very problematic. Demand for new competitive pressures and service-oriented, knowledge-based economy mean 'manual auditing' is becoming a diminishing option for successful auditors. Associated with the view that IT auditing is the dominant training issue amongst most auditors, SOA environment has added an influential conceptual vocabulary to analyse auditing strategies. This research found such approaches being criticised for underestimating the complex relations between 'interests of ownership' and 'quality of audit'. Interviewers for this qualitative research uncovered that contemporary locus of auditors have become personalised rather than generalised, through the spread of corporate cultures, panoptic surveillance, and self-discipline. Evidence here shows auditors are experiencing considerable problems with audit quality within an SOA environment.